Die Bedeutung sozialer Medien für die Praxis der Berufsbildungsforschung - Getz, Laura [Verfasser] (My University, 2024)
„Der Themenkomplex Social Media ist in der Berufsbildungsforschung bisher aus der Perspektive von Ausbildungspersonal (vgl. Hähn/Ratermann-Busse 2020; Breiter et al. 2018), Berufsschüler*innen (vgl. Jahncke et al. 2020), Politikschaffenden oder Eltern von Berufsschüler*innen (vgl. Aufenanger 2018) betrachtet worden. Die Perspektive der Berufsbildungsforschenden, ihre Einstellungen zu sozialen Medien sowie ihre wissenschaftskommunikativen Praktiken waren bislang jedoch nicht Gegenstand der Forschung. In Anbetracht der fortschreitenden Digitalisierung von Wissenschaftskommunikation (vgl. Bonfadelli et al. 2017; Taubert/Weingart 2016) und einer zunehmenden „Öffentlichkeitsorientierung der Wissenschaft“ (Fähnrich/Schäfer 2020, 517) ist ein Blick auf die Nutzung sozialer Medien in der Berufsbildungsforschung geboten. Spielen doch der Transfer wissenschaftlicher Erkenntnisse dieses Gegenstandsbereiches in die Praxis (vgl. Euler 2008, 65) und der Transfer zwischen Wissenschaft und Politik (vgl. Weingart 2001) eine zentrale Rolle bei der Bewältigung gesellschaftlicher Herausforderungen (vgl. Bonfadelli et al. 2017, 3ff.). Außerdem ist anzunehmen, dass Berufsbildungsforschende durch die zunehmende Nutzung von Social-Media-Plattformen in der Wissenschaftskommunikation (vgl. Sugimoto et al. 2017; Donelan 2016) und dem potenziellen Nutzen der Plattformen für einzelne Wissenschaftler*innen (vgl. Carrigan 2020) soziale Medien für die Vermarktung ihrer Forschungsergebnissen nutzen oder nutzen möchten.“ (Autorenreferat; BIBB-Doku)

„Within Vocational Education and Training (VET) research, social media has been explored from the perspective of teachers (cf. Hähn/Ratermann-Busse 2020; Breiter et al. 2018), apprentices (cf. Jahncke et al. 2020), policy-makers and the parents of apprentices (cf. Aufenanger 2018). However, the perspective of VET researchers, their attitudes towards social media and their research communication practices have not yet been explored. Against the background of an increasing digitalisation of research communication (cf. Bonfadelli et al. 2017; Taubert/Weingart 2016) and growing efforts to enhance external research communication (cf. Fähnrich/Schäfer 2020, 517), it appears necessary to investigate the use of social media in VET research specifically. After all, the transfer of research results from VET research into VET practice (cf. Euler 2008, 65) and from research into politics (cf. Weingart 2001) play a crucial role in overcoming societal challenges (cf. Bonfadelli et al. 2017, 3ff.). Due to the increasing use of social media platforms in research communication in general (cf. Sugimoto et al. 2017; Donelan 2016) and the potential benefits of social media use for individual researchers (cf. Carrigan 2020), VET researchers presumably strive to use social media to disseminate their research results and thereby enhance their success as individual researchers (cf. Carrigan 2020). The dissertation project explores how VET researchers use social media and what factors influence their research communication practices. This paper outlines the explorative and ethnographic approach applied in the project to uncover how social media are a part of the everyday work life of VET researchers. The research design consists of three phases, each applying a qualitative approach embedded in an ethnographic methodology. Four rounds of questions with VET researchers were followed by an online ethnography (cf. Bareither/Schramm 2023; Hine 2020; Marotzki 2017; Pink 2017; Breidenstein et al. 2013) on Twitter and ResearchGate. The online ethnography was then followed by semi-structured interviews with VET researchers. This article outlines findings from the field research phase of the online ethnography, as well as initial findings from the interview phase. It also discusses the results with regard to the relevance of social media for work practices within VET research.“ (author’s abstract; BIBB-Doku)
The relevance of social media for the professional practice of VET research
Keywords: T 1 Forschungsrichtungen; 370; 300; Berufsbildungsforschung; Wissenschaftler; Wissenschaftskommunikation; Social Media; Mediennutzung; Wissenschaftliches Arbeiten